Attitude of Extension Professionals Towards Agri-Expert Systems - Ravikishore, Modem; Jacob, Reeba; Thomas, Allan (International Journal of Bio-resource and Stress Management, 2023)
It has been suggested that ‘agri-expert systems’ might have a significant role in the future by enabling large number of people so that they can access human experts. It is, therefore, important to understand how potential users interact with these computer systems. This study investigates the extension professionals’ attitude towards the use of Kerala Agricultural University (KAU) expert systems for fertilizer recommendation, pest, disease diagnosis, and management of weeds in crop fields. The study also depicts the factors affecting the attitude of extension professionals. A survey was conducted among three targeted segments of Kerala’s extension professionals with a sample of 100 respondents actively involved in the field of agriculture to evaluate questions about the attitude of respondent in using agri-expert systems. It also aims to depict the factors which are affecting the attitudes of extension professionals. Results showed that the extension professionals’ attitude towards agri-expert systems was generally moderately favorable and the factors such as Training, Innovative proneness and Information content were positively and significantly related with the attitude towards expert systems among all three categories of respondents. In order to improve the extension professionals’ attitude towards expert systems, information content available in the expert system should be up to date and addresses the problems which are location specific and need specific. There is also greater need to enrich extension professionals’ knowledge about the innovative applications of expert systems by conducting suitable training programmes in a timely manner for the benefit of farming community and effective agriculture decision making.